Alkali and alkaline-earth metal ion–solvent co-intercalation reactions in nonaqueous rechargeable batteries. Issue 46 (12th November 2021) - Li, Lin; Hu, Zhe; Zhao, Shuo; Chou, Shu-Lei
Abstract : This review summarizes the recent progress of alkali and alkaline-earth metal ion–solvent co-intercalation reactions in nonaqueous rechargeable batteries. Abstract : Alkali and alkaline-earth metal ion–solvent co-intercalation reactions have attracted extensive attention in recent years owing to the advantage of the absence of a desolvation process, which generally results in fast kinetics and good rate performance for batteries. However, less attention has been paid to summarizing the mechanism, performance and other related aspects about ion–solvent co-intercalation reaction in batteries. A summary of alkali and alkaline-earth metal ion–solvent co-intercalation reactions in nonaqueous rechargeable batteries is presented in this review, which mainly focuses on the electrochemical performance, ion–solvent co-intercalation mechanism, conditions for reversible ion–solvent co-intercalation and potential for practical application. It is suggested that future research should focus on reducing the redox potential of the ion–solvent co-intercalation reaction to achieve high energy-density and power-density full cells. This review provides an understanding of alkali and alkaline-earth metal ion–solvent co-intercalation reactions in nonaqueous rechargeable batteries and will serve as significant guidance for researchers to further develop ion–solvent co-intercalation reactions for fast-charging batteries.